2014
DOI: 10.24059/olj.v18i2.399
|View full text |Cite
|
Sign up to set email alerts
|

Good Quality Discussion is Necessary but Not Sufficient in Asynchronous Tuition: A Brief Narrative Review of the Literature

Abstract: The growth of online learning within education has corresponded to an increase in use of asynchronous discussion. Asynchronous discussion is a form of interaction that is mediated rather than directed, and is characterized by a time lag in the interactions between discussants. In this paper we conducted a brief narrative review of the literature on asynchronous discussion. We argue, initially, that discussion is necessary, but not sufficient, for successful pedagogic outcomes-especially in the case of online l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Clarke and Bartholomew (2014) reached similar results, though they noted in their analysis of instructors' participation in online discussions that instructors overwhelmingly provided comments that were encouraging, positive, and reaffirming, while students wanted more feedback and "constructive criticism that would lead to new understanding of content" (p. 19). Additionally, several authors found effective the use of bi-and tri-level questions, and their work potentially supports our findings for engaged learning: Level 1 questions are those where the answer can be found in course materials; Level 2 questions require students to relate materials to a personally relevant answer (using their personal experiences); and Level 3 questions ask students to find connections between course materials and broader social contexts (Fear & Erikson-Brown, 2014;York & Richardson, 2012). While professors can create some of the aspects and environment needed for such engaging discussion experiences, support from the university also might be necessary, including resources to assist instructors with feedback and assessment and training students in appropriate ways to craft, share, and receive diverse opinions in a classroom setting.…”
Section: Recommendationssupporting
confidence: 82%
See 2 more Smart Citations
“…Clarke and Bartholomew (2014) reached similar results, though they noted in their analysis of instructors' participation in online discussions that instructors overwhelmingly provided comments that were encouraging, positive, and reaffirming, while students wanted more feedback and "constructive criticism that would lead to new understanding of content" (p. 19). Additionally, several authors found effective the use of bi-and tri-level questions, and their work potentially supports our findings for engaged learning: Level 1 questions are those where the answer can be found in course materials; Level 2 questions require students to relate materials to a personally relevant answer (using their personal experiences); and Level 3 questions ask students to find connections between course materials and broader social contexts (Fear & Erikson-Brown, 2014;York & Richardson, 2012). While professors can create some of the aspects and environment needed for such engaging discussion experiences, support from the university also might be necessary, including resources to assist instructors with feedback and assessment and training students in appropriate ways to craft, share, and receive diverse opinions in a classroom setting.…”
Section: Recommendationssupporting
confidence: 82%
“…Enabling understanding of diverse perspectives. This reflective learning is not easy to achieve, as noted by others (see Fear & Erikson-Brown, 2014). Yet students in our study, similar to those in others' research, noted that they not only enjoyed hearing others' views during online discussions, but appreciated expanding their own viewpoints.…”
Section: Deep Learningmentioning
confidence: 88%
See 1 more Smart Citation
“…Several modern computer-mediated communication (CMC) technologies can be utilized in online courses for the purpose of increasing collaborative interactions among the participants. Concurrently, the use of an asynchronous discussion forum (DF) is increasing in asynchronous Computer Science Students' Attitudes Towards the Use of Structured and Unstructured Discussion Forums in Fully Online Courses online learning (Fear & Brown, 2014;Zhou, 2015). Asynchronous DFs play a substantial role in humanizing online courses by replicating the classroom experience of information exchange and community building, not just between students and their instructor but also among the students themselves (Saadé & Huang, 2009).…”
Section: Computer Science Students' Attitudes Towards the Use Of Strumentioning
confidence: 99%
“…Participation in a DF demands that students become actively engaged with the course content and learning activities. Through interaction with their peers, students learn to negotiate the meaning of the content (Fear & Brown, 2014;Serena, 2009). DFs also allow the creation of collaborative knowledge, since learners work together, exchange information, share resources and ideas, and comment on each other's work (Gao, 2014;Preece, 2000;Serena, 2009).…”
Section: Review Of Related Literaturementioning
confidence: 99%